DIGITAL MARKETPLACE IN SMEs SUSTAINABILITY - Oktaviani, Intan; Triana (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The application of the K-Means algorithm in digital marketplaces is an effective data analysis strategy for grouping customers, products or reviews based on certain characteristics. In the context of digital marketplaces, K-Means is used to understand customer behavior, improve the shopping experience, and optimize business operations. This article describes the basic concept of implementing K-Means in a digital marketplace, including implementation steps and benefits that can be obtained. This method helps marketplaces in customer segmentation, product recommendations, sentiment analysis, and data-driven decision making. By using K-Means, digital marketplaces can optimize marketing strategies, product and service offerings, and increase overall customer satisfaction. In conclusion, the K-Means algorithm is an important tool in data analysis that supports the growth and success of digital marketplaces in the ever-developing digital era.